Kredensial Mikro dalam Spektrum Teknologi Pendidikan: Implementasi dan Keselarasan dengan Definisi AECT - Hafida Ruminar; Dedi Kuswandi; Otto Fajarianto (Institut Agama Kristen Negeri (IAKN) Ambon, 2025)
Abstract: Changes in the evolving demands of the global workforce have prompted the higher education sector to respond through micro-credential programs, which aim to bridge the gap between formal education and industry. This study seeks to analyze the alignment between the implementation of micro-credentials in Indonesia and the latest definition of educational technology approved by the Association for Educational Communications and Technology (AECT) in 2023. Using a descriptive qualitative approach through literature review, the study examines policy documents, reports from international organizations, and scientific articles published within the last five years. The findings reveal that micro-credentials in Indonesia demonstrate strong alignment in the dimensions of performance improvement and strategic design, partial alignment in learner empowerment, and significant gaps in the ethical dimension, particularly concerning data privacy and equity of access. The study concludes that micro-credentials in Indonesia are on the right track, but greater emphasis is needed on data governance, quality assurance, and curriculum integration to achieve full alignment with the AECT 2023 paradigm. Keywords: Micro-Credentials, Educational Technology, Learner Empowerment, Strategic Design, Ethics